Job: A Masque for Living: Creativity as Palimpsest - Boyce-Tillman, June (Usuteaduslik Ajakiri, 2020)
This article draws on an artistic presentation using audio, visual and live artistic elements to explore theodicy through the twenty-two plates for the Book of Job of William Blake dating from 1821 or 1822, Vaughan Williams’s Job—A Masque for dancing and a song by June Boyce-Tillman drawing in the Wisdom theology of William Brown. It will use the image of the palimpsest as a metaphor for an artist’s creative process. This starts with de Quincey’s (1998) work on art as resurrection, Plato’s and Freud’s (1925) work on memory as a wax tablet, Kristeva’s intertextuality with the distinction between the geno-text and pheno-text (Johnson 1988) and Buber’s (1970) and Williams’s (2018) on art as encounter, which are combined with Koestler’s (1964) work on the incubation phase in the creative process (Wallas 1926). It will examine the different possibilities and limitations of various art forms. Blake, influenced by Swedenborg and Boehme, used the story to construct a symbolic universe in line with his thinking about the important role of the imagination in the spiritual search, limited for him by the new natural sciences and traditional religion. These illustrations were taken up by the composer Vaughan Williams as the basis of Job—A Masque for dancing—from 1931, of which pieces were played in the presentation, such as Satan’s Dance of Triumph and the Pavane of the Heavenly Host. The work of William Brown in Wisdom’s Wonder (2014) was also included in the thinking behind June Boyce-Tillman’s Forgiveness Song (2018), which is set out to show how the artistic sources were reworked in a new way that allows the former artworks to shine through. The article intertwines theodicy in Job with explorations of the complex nature of the creative process.